Mediations and socio-digital interactions related to self-medication among young university students in Mexico - Sevillano Hernández , Coralia Nicole (2024)
In October 2019, several social sectors in Ecuador, including members of indigenous organizations, transportation workers, and students, paralyzed the country for eleven days due to the economic reforms proposed by former President Lenín Moreno Garcés. This research examines the extent of the dissemination of journalistic content in community media in the province of Imbabura. A mixed methodology was employed, utilizing survey techniques directed at the inhabitants of Imbabura (quantitative paradigm) and semi-structured interviews with experts (qualitative paradigm). The results highlight that community media generated more trust among the population than private media, despite their limited presence in the province and the low financial resources they have, thus becoming a source of information for the population. This social event reflected the need for media outlets that give voice to local and rural communities, promoting a more comprehensive and equitable information landscape enriched by diversity and interculturality.